JHEA, Volume 11, n°1 & 2, 2013 - Full Issue - journal system, (Journal of Higher Education in Africa, 2013)
Contents Continuity and Change in Students’ Account of Race and Class Relations at a South African University Deevia Bhana .....................................1 Funding Higher Education in Africa: State, Trends and Perspectives Damtew Teferra ........................................19 Towards Evaluating a Higher Education Residence Environment that is Conducive to Learning, Development and Success Willem Petrus Wahl ..................................53 Reengineering Postgraduate Curricula and its Mode of Delivery: Graduate Students’ Views of Modular Course Delivery at Addis Ababa University Solomon Areaya, Ayalew Shibeshi & Daniel Tefera ....................71 Massive Open Online Courses (MOOCs) and Green Economy Transition: Feasibility Assessment for African Higher Education Godwell Nhamo ................................103 The History of Makerere Institute of Social Research (MISR) and Her Place in the Study of the Social Sciences in Africa Stanley Baluku Bakahinga Mbalibulha.................................123 The British Model, ‘Africanization’ of the Curriculum and other Issues: The Influence of Professor D. W. Ewer (1913-2009) on University Teaching in Ghana and on Biological Education in Africa Richard Alan Baker ...................................... 145 “...University is ISO 9000:2008 Certified”: Neoliberal Echoes, Knowledge Production and Quality Assurance in Kenyan State Universities Ishmael I. Munene .........................................163